(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mindfulness-based interventions (MBIs) have gained prominence as effective, non-pharmacological treatments for managing anxiety and stress, particularly in individuals with psychiatric disorders such as depression, post-traumatic stress disorder (PTSD), and generalized anxiety disorder (GAD). This review examines the impact of MBIs, including Mindfulness-Based Stress Reduction (MBSR) and Mindfulness-Based Cognitive Therapy (MBCT), on anxiety and stress reduction in patients with psychiatric conditions. The mechanisms underlying MBIs involve cultivating present-moment awareness, enhancing emotional regulation, and reducing rumination, which collectively contribute to improved mental health outcomes. A comprehensive analysis of existing literature, including randomized controlled trials (RCTs), indicates that MBIs significantly reduce anxiety and stress levels, with moderate to large effect sizes. Patients also reported increased resilience, improved mood, and enhanced coping skills. While the short-term effects of mindfulness interventions are promising, the long-term sustainability of these benefits remains under-explored, and variability in study designs, intervention duration, and patient adherence presents challenges to standardizing outcomes. Despite these limitations, MBIs offer a low-risk, accessible, and cost-effective approach to mental health care, complementing conventional treatments like medication and psychotherapy. This review highlights the need for more rigorous, long-term studies to further investigate the potential of MBIs as integrated components of psychiatric treatment. By providing a holistic and patient-centered approach to managing anxiety and stress, MBIs hold significant promise for improving the quality of life for individuals with psychiatric disorders, offering an alternative pathway to mental health recovery.